2009
DOI: 10.1002/fam.1012
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of a phosphorus‐based FR, a nanoclay and PA6. Part 2 interaction of the complete PA6 polymer nanocomposites

Abstract: SUMMARYPolyamide 6 (PA6) is modified with a nanoclay (NC), Cloisite 30B and/or a flame retardant (FR), OP1311. The thermal decomposition of pure PA6 and PA6 nanocomposites is done by thermogravimetric analysis (TGA). The decomposition products from TGA in nitrogen and air are analysed online by Fourier transform infrared (FTIR) spectroscopy in order to examine the time/temperature-dependent thermal degradation processes and monitor the evolved gases online. The profiles of the evolved gases are compared with -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 14 publications
1
10
1
Order By: Relevance
“…The presence of AlPi and clay appears only to have a slight maximum rate suppressing effect when both are present especially in the core (Sample 9). This single TGA volatilisation stage under nitrogen or vacuum conditions has been noted and reviewed by other authors [29,30,31,32]. For example, Kamerbeek et al [31] showed that volatiles such as NH3 (via its elimination during amine end interactions) and CO2…”
Section: Figurementioning
confidence: 75%
“…The presence of AlPi and clay appears only to have a slight maximum rate suppressing effect when both are present especially in the core (Sample 9). This single TGA volatilisation stage under nitrogen or vacuum conditions has been noted and reviewed by other authors [29,30,31,32]. For example, Kamerbeek et al [31] showed that volatiles such as NH3 (via its elimination during amine end interactions) and CO2…”
Section: Figurementioning
confidence: 75%
“…Several studies confirmed this speculation that the alkylphosphinate‐based flame retardant and OMMT did have a synergistic effect on polyamide 6 (PA6) . Ramani et al systematically investigated the interaction of a phosphorus‐based flame retardant, a nanoclay, and PA6 and found that the addition of the phosphorus‐based flame retardant and the nanoclay in PA6 seemed to have a synergistic effect on the thermal decomposition of PA6. Isitman et al found that substitution of a certain fraction of the flame retardant (based on phosphorus compounds and zinc borate) with nanoclays can significantly reduce the peak heat release rate (PHRR) and delay ignition time of short (glass fiber)‐reinforced PA6, and the enhanced flame retardancy of nanocomposite formulations was ascribed to the formation of a glassy boron/(aluminum phosphate) barrier reinforced by clay layers at the nanoscale .…”
Section: Introductionmentioning
confidence: 93%
“…According to the acting mechanism of alkylphosphinate‐based flame‐retardant systems, one can imagine that the potential flame‐retardant synergism might exist between aluminum phosphinates and organic montmorillonite (OMMT), because OMMT has been widely used as a flame retardant by the formation of multilayered carbonaceous‐silicate barrier on the polymer surface that will insulate the underlying material from the heat flux of the flame and act as a mass transport barrier . Several studies confirmed this speculation that the alkylphosphinate‐based flame retardant and OMMT did have a synergistic effect on polyamide 6 (PA6) . Ramani et al systematically investigated the interaction of a phosphorus‐based flame retardant, a nanoclay, and PA6 and found that the addition of the phosphorus‐based flame retardant and the nanoclay in PA6 seemed to have a synergistic effect on the thermal decomposition of PA6.…”
Section: Introductionmentioning
confidence: 99%
“…The aluminum and boron phosphates enhance the stability of the residue by means of forming a barrier and protect the underlying polymer against the fire. Aluminum phosphinate can promote PA6 to form a char layer so as to stop heat transfer and decrease onset temperature of thermal degradation 25. AlHP also is a good flame retardant for PA6 and glass fiber reinforced PA6 26.…”
Section: Introductionmentioning
confidence: 99%